Implementasi Metode Hierarchical Token Bucket (HTB) pada Pembagian Bandwith Berdasarkan Media Pembelajaran Online dan Social Media - Dicky Anggara Sendiyono; Dian Widiyanto Chandra (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Education in Indonesia is growing rapidly, schools provide the internet for learning activities by accessing educational content that has been created by schools through online learning media. SMP Stella Matutina Salatiga as a case study place, in learning activities using online learning media is not optimal because many school residents use the internet to access social media. To overcome this problem, it is necessary to manage internet bandwidth by implementing the Hierarchical Token Bucket (HTB) method. This bandwidth distribution aims to facilitate learning activities, where bandwidth will be prioritized for online learning media. By dividing the bandwidth using the HTB method, the bandwidth is more organized. The results of the test were carried out by measuring the QoS parameters using video streaming services and interactive services which experienced an increase in network quality after the HTB method was applied, it was marked by a decrease in the average value of jitter, delay, and packet loss, which means the throughput obtained is greater. The application of the HTB method is of course learning to use online learning media to be more optimal.